Exponential discounting bias - Gomes, O. (2014)
We address intertemporal utility maximization under a general discount function that nests the exponential discounting and the quasi-hyperbolic discounting cases as particular specifications. The suggested framework intends to capture one important piece of behavioral evidence typically found when addressing the way agents discount the future, namely the evidence pointing to the prevalence of decreasing impatience. Decreasing impatience can be perceived as a bias relatively to what would be a benchmark exponential discounting setting, and is modeled as such. The general discounting framework is used to approach a standard optimal growth model in discrete time. Transitional dynamics and stability properties of the corresponding dynamic setup are studied. An extension of the standard utility maximization model to the case of habit persistence is also considered.